Elongation rate and average length of amyloid fibrils in solution using isotope-labelled small-angle neutron scattering. Issue 4 (11th June 2021) - Eves, Ben J.; Doutch, James J.; Terry, Ann E.; Yin, Han; Moulin, Martine; Haertlein, Michael; Forsyth, V. Trevor; Flagmeier, Patrick; Knowles, Tuomas P. J.; Dias, David M.; Lotze, Gudrun; Seddon, Annela M.; et al.
Abstract : We demonstrate a solution method that allows both elongation rate and average length of amyloid fibrils to be independently determined. Abstract : We demonstrate a solution method that allows both elongation rate and average fibril length of assembling amyloid fibrils to be estimated. The approach involves acquisition of real-time neutron scattering data during the initial stages of seeded growth, using contrast matched buffer to make the seeds effectively invisible to neutrons. As deuterated monomers add on to the seeds, the labelled growing ends give rise to scattering patterns that we model as cylinders whose increase in length with time gives an elongation rate. In addition, the absolute intensity of the signal can be used to determine the number of growing ends per unit volume, which in turn provides an estimate of seed length. The number of ends did not change significantly during elongation, demonstrating that any spontaneous or secondary nucleation was not significant compared with growth on the ends of pre-existing fibrils, and in addition providing a method of internal validation for the technique. Our experiments on initial growth of alpha synuclein fibrils using 1.2 mg ml −1 seeds in 2.5 mg ml −1 deuterated monomer at room temperature gave an elongation rate of 6.3 ± 0.5 Å min −1, and an average seed length estimate of 4.2 ± 1.3 μm.